Nafion®-Containing Solid Lipid Nanoparticles as a Tool for Anticancer Pt Delivery: Preliminary Studies - Maddalena Sguizzato; Elisabetta Esposito; Marcus Drechsler; Eleonora Gallerani; Riccardo Gavioli; Paolo Mariani; Federica Carducci; Rita Cortesi; Paola Bergamini (Journal of Chemistry)
Preliminary studies of nanoparticles based on the perfluorosulfonic acid resin Nafion have been carried out with the aim of establishing an ionic connection with the protonable phosphine 1,3,5-triaza-7-phosphaadamantane (PTA), suitable for the coordination of platinum. Nafion-containing nanoparticles (NAF) were produced by homogenization followed by ultrasonication method. After production, NAF were characterized in terms of size, morphology, and in vitro cytotoxicity. The PCS studies showed that the Z-average mean diameter was around 250 nm. Moreover, the polydispersity index showed a monodimensional distribution of nanoparticles. Cryo-TEM analysis showed a uniform and homogenous population of particles, characterized by the presence of both ovoidal and needle-like structures. To evaluate the in vitro cytotoxicity, NAF were tested on human cancer cell lines K562 and A2780. No cytotoxic effect was found on both cell lines. By 13P-NMR measures, it is here proved that the strongly acidic sulfonic groups of Nafion-containing nanoparticles (NAF) can act as protonating agents for PTA. The protonation occurs selectively at nitrogen; hence protonated PTA maintains its ability to coordinate platinum via its phosphorus atom.